Thrombolysis in patients older than 80 years with acute ischaemic stroke: Canadian Alteplase for Stroke Effectiveness Study. - Sylaja, P; Cote, R; Buchan, A; Hill, MD (2006)
BACKGROUND: The benefit of intravenous tissue plasminogen activator (tPA) given within 3 h of acute ischaemic stroke to patients over 80 years of age is uncertain. AIM: To examine the clinical characteristics and complications and the predictors of outcome after intravenous tPA treatment in patients aged > or = 80 years. METHODS: Data (n = 1135) prospectively collected from the Canadian Alteplase for Stroke Effectiveness Study were reviewed and patients aged > or = 80 years (n = 270) treated with intravenous tPA for acute ischaemic stroke were compared with those aged <80 years (n = 865). RESULTS: The risk of symptomatic intracerebral haemorrhage did not differ between patients aged > or = 80 years and <80 years (4.4% (95% CI 2.3 to 7.6) v 4.6% (95% CI 3.3 to 6.2), p = 1.0). Favourable outcome, defined as a modified Rankin Score of 0-1 at 90 days, was seen in 26% of patients aged > or = 80 years and in 40% of those <80 (p<0.001). The following baseline characteristics were found to be more common in those aged > or = 80 years than in those aged <80 years: atrial fibrillation (37% v 18%; p<0.001); congestive heart failure (11% v 6%; p = 0.004); hypertension (59% v 48%; p = 0.002); and severity of stroke with a median National Institutes of Health Stroke Scale (NIHSS) score of 16 v 14 (p = 0.004). In the multivariable logistic regression analysis, age > or = 80 years, stroke severity, baseline Alberta Stroke Program Early CT Score and glucose level were found to be the major independent predictors of outcome. CONCLUSION: In carefully selected elderly patients, the use of intravenous tPA was not found to be associated with an increased risk of symptomatic intracerebral haemorrhage. Age-related differences were seen in the clinical characteristics and outcome in the elderly population.